Pricing Efficiency of Exchange Traded Funds in India - Reddy, Y V; Dhabolkar, Pinkesh (Organizations and Markets in Emerging Economies, 2020)
Exchange traded funds (ETFs) have two prices, the market price and the net asset value (NAV) price. ETFs NAV price gets determined by the net value of the constituent assets, whereas the market price of ETFs depends upon the number of units bought or sold on the stock exchange during trading hours. As per the law of one price, the NAV and market price of the ETF should be the same. However, due to demand and supply forces, the market price may divert from its NAV. This price difference may have significant repercussions to investors, as it represents a cost if they buy overvalued ETF shares or sell undervalued ETF shares. Pricing efficiency is the speed at which the market makers correct the deviations between ETFs NAV and market price. The present study attempts to investigate the pricing efficiency of Indian equity ETFs employing an autoregression model over its price deviation, and also attempts to understand the lead-lag relationship between the price and NAV using the vector error correction model (VECM).
Keywords: exchange-traded funds; pricing efficiency; premium; discount